A Note on Reform Reversals and Output Growth in Transition Economies - Bruno Merlevede (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2000)
The abandonment of central planning led to considerable output declines in countries in the firmer soviet-bloc. The magnitude and length of the output declines, as well as recovery experiences have been very diverse. Various detfirminants of outpt growth have been identified in the literature. One of most important elements in the traditional phase is the evolution to the market system. The closer an economy to a marketsystem, the more beneficial effects on growth expected.
Keywords: 330; Wirtschaftswachstum; Übergangswirtschaft; Wirtschaftliche Anpassung; Systemtransformation; Osteuropa; GUS-Staaten